2019
DOI: 10.2516/ogst/2019016
|View full text |Cite
|
Sign up to set email alerts
|

Application of Particle Swarm Optimization (PSO) algorithm for Black Powder (BP) source identification in gas pipeline network based on 1-D model

Abstract: Black Powder (BP) is a worldwide challenge that spans all stages of the natural gas industry from the producing wells to the consuming points. It can endanger the pipeline operations, damage instruments and contaminate customer supplies. The formation of BP inside natural gas pipeline mainly results from the corrosion of internal walls of the pipeline, which is a complex chemical reaction. This work aims to develop a novel algorithm for BP source identification within gas pipelines network based on a 1-D model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is also important to mention that the solution of the proposed LT-based BP sources concentrations estimation approach as well as the other optimization base approaches is unique, and it is valid if and only if the number of measurements devices is equal to the unknown sources [30].…”
Section: ) Bp Estimation Methods Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to mention that the solution of the proposed LT-based BP sources concentrations estimation approach as well as the other optimization base approaches is unique, and it is valid if and only if the number of measurements devices is equal to the unknown sources [30].…”
Section: ) Bp Estimation Methods Comparisonmentioning
confidence: 99%
“…Geometric parameters and flow conditions for 15-pipe gas network[30]. Simulated real values of BP concentration at each source.…”
mentioning
confidence: 99%
“…Previous research works also confirmed the efficiency of using the PSO algorithm and LSTM neural networks in solving complex engineering problems. 34 39 The PSO algorithm is based on a simple design and provides strong global search ability and fast convergence and hence is often used to solve various complex optimization problems. 40 , 41 In this paper, we use the PSO algorithm to optimize the training parameters in the LSTM model, accelerate the convergence speed of the model, reduce the training time, and improve the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Pipeline networks are the most common means of natural gas transportation. They are thus being constructed on a large scale in recent years [3]. The scale of natural gas pipeline networks is becoming increasingly larger and the topological structure is becoming increasingly more complex [4].…”
Section: Introductionmentioning
confidence: 99%